Home

About

Advanced Search

Browse by Discipline

Scientific Societies

E-print Alerts

Add E-prints

E-print Network
FAQHELPSITE MAPCONTACT US


  Advanced Search  

 
x, y Cn x -iy ix + y x = iy
 

Summary:  Һ
x, y Cn

x - iy ix + y x = iy
x + iy ix + y |x| = |y| x y ׺
׺ (x-iy) (ix+y) и ܵ
(x-iy) (ix+y) = (x-iy) (i(x-iy)) = i((x-iy) (x-iy)) = 0
޸ x-iy = 0 x = iy
ظ
ص (x+iy)(ix+y) = x(ix)+(iy)(ix)+xy+(iy)y = i(xx-yy)+(yx+xy) = 0
и vv ׸ xy = y x
x y к 0
0 к ׸
|x| = |y| и x y ׺
u Cn
u ָ u
H Cn
H = {v | v H}
U Cn
U Cn

  

Source: goston, Istvn - Institute of Mathematics, Etvs Lornd University

 

Collections: Mathematics